Examining the Influence of Artificial Intelligence between Burnout, Employee Performance in Higher Education - Zainuddin, Erikson Saragih, Salman Faris, Maria Linda (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Higher education is just one of several sectors that have seen a meteoric rise in the AI integration rate in recent years. Within the setting of academic institutions, this literature review seeks to investigate the effects of artificial intelligence on burnout and productivity among staff members. Academic burnout, which impacts health and work satisfaction, is on the rise and is defined by emotional tiredness, depersonalization, and diminished personal achievement. However, educational institutions and the quality of education they provide are highly dependent on the performance of their employees. In the first part of the study, we take a look at the big picture of artificial intelligence (AI) in higher education and how it may improve administrative duties, learning experiences (via personalized suggestions), and decision-making. There are worries that workers will be displaced from their jobs, have their responsibilities altered, and have more work to complete as a result of AI's fast adoption.